Assessing Legal Protection Effectiveness for Women Facing Digital Sexual Violence - Purnama Pratiwi, Putri Fransiska; A. Saiful Aziz; Fransiskus Saverius Nurdin; Gunarto; Maggouri Abdelaali (Lembaga Contrarius Indonesia, 2025)
The Electronic Information and Transactions Law functions as the principal legal framework for addressing online gender-based sexual violence in Indonesia; however, legal and structural weaknesses within this framework continue to obstruct the achievement of effective legal protection for victims. This study critically examines both the normative construction and empirical implementation of the ITE Law in order to formulate a more victim-oriented model of legal protection for individuals affected by online sexual violence. The research applies a constructivist paradigm through an empirical juridical method and utilizes a socio-legal approach supported by statutory and case-based analyses. This study identifies three principal findings. First, Article 27 paragraph (1) of the ITE Law prioritizes the regulation of digital content over victim protection, thereby weakening the victim-centered approach to online gender-based sexual violence. Second, the reliance on electronic document-based evidence, coupled with persistent victim-blaming practices, constrains the fulfillment of victims’ restitution rights and weakens their procedural legal position. Third, patriarchal cultural dominance sustains social stigma against female victims and discourages access to legal remedies. Based on these findings, this study proposes regulatory reform through the insertion of the phrase “with consent,” reclassification of offenses to protect victim identity, and strengthening public awareness of digital privacy to ensure effective and equitable legal protection.